2016
DOI: 10.1159/000443080
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant, Anti-Inflammatory and Anti-Apoptotic Activities of the Bauhinia Championii Flavone are Connected with Protection Against Myocardial Ischemia/Reperfusion Injury

Abstract: Background/Aims: Previous studies have demonstrated that Bauhinia championii flavone (BCF) exhibits anti-oxidative, anti-hypoxic and anti-stress properties. This study was designed to investigate whether BCF has a cardioprotective effect against myocardial ischemia/reperfusion (I/R) injuries in rats and to shed light on its possible mechanism. Methods: The model of I/R was established by ligating the left anterior descending coronary artery for 30 min, then reperfusing for 180 min. Hemodynamic changes were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…In addition, inhibiting inflammation can decrease myocardial I/R injury and preserve cardiac function [32, 33]. In the present study, we found that preconditioning of troxerutin reduced the production of inflammatory cytokines induced by I/R injury.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, inhibiting inflammation can decrease myocardial I/R injury and preserve cardiac function [32, 33]. In the present study, we found that preconditioning of troxerutin reduced the production of inflammatory cytokines induced by I/R injury.…”
Section: Discussionsupporting
confidence: 64%
“…Subsequently, activation of TLR4 can activate NF-κB via MyD88-dependent pathway or MyD88-independent pathway leading to the production of inflammatory cytokines [14,27]. It is demonstrated that inhibition of TLR4 signaling pathways can attenuate inflammatory response and cardiac myocyte apoptosis following myocardial I/R injury [28][29][30]. In our study, we found that I/R could up-regulated the mRNA levels of TLR4, HMGB-1, MyD88, and NF-κB (p65), whereas down-regulated IKB-α, which agrees with a previous report [31].…”
Section: Discussionmentioning
confidence: 99%
“…When the ER stress occurs, ROS can be elevated to induce the neighboring mitochondria for accentuating the onset of intrinsic apoptosis [59]. Flavone, as the antioxidant can protect myocardial ischemia/reperfusion injury anti-apotosis effect [60]. …”
Section: Ros Trigger Apoptosismentioning
confidence: 99%